2005
DOI: 10.1007/s00401-005-1030-8
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of heat shock proteins in pallido-nigral axonal spheroids of nonhuman aged primates

Abstract: The occurrence of spheroids has been described in the globus pallidus (GP) and substantia nigra pars reticulata (SNr) of aged rhesus monkeys. Opinions vary as to the origin of spheroids. Ultrastructural and immunohistochemical analysis suggested that spheroids originate from degenerating axons or astroglia. In the present study, we have investigated the GP and SNr of aged monkeys (Macaca fascicularis and Macaca mulatta). Although immunoreactive for microtubule-associated protein (MAP) 1A, tau, amyloid precurso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Preparation of brain sections and immunostaining were performed according to a procedure previously described 21,26 . Sliced sections were incubated with the primary antibodies and visualized by Alexa 555-conjugated anti-rabbit IgG, Alexa 488-conjugated streptavidin (Invitrogen, This article has been peer-reviewed and accepted for publication, but has yet to undergo copyediting and proof correction.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Preparation of brain sections and immunostaining were performed according to a procedure previously described 21,26 . Sliced sections were incubated with the primary antibodies and visualized by Alexa 555-conjugated anti-rabbit IgG, Alexa 488-conjugated streptavidin (Invitrogen, This article has been peer-reviewed and accepted for publication, but has yet to undergo copyediting and proof correction.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…One report indicated that no difference in MAP-2 and SYN was observed between young adult (5-year) and old (18-year) nonhuman primates; however, there were only two old animals in the study and the analysis was performed in the pallidonigral region (Fukuda et al 2005). However, since rhesus macaques in captivity can live longer than 30 years (Uno et al 1996), the current study includes much older animals and examined cortical regions linked to cognitive function.…”
mentioning
confidence: 95%
“…Large quantities of lipofuscin deposits in all animals and large granules across an extensive area were observed. Axonal spheroids that were identified as “Pallido-nigral axonal spheroids” (Fukuda et al 2005) were observed in the globus pallidus of the basal ganglia in all animals. These findings were significantly increased in middle-aged monkeys when compared with young monkeys.…”
Section: Discussionmentioning
confidence: 99%